PEMBUATAN DAN PENGEMBANGAN LAMPU LED CELUP (SUPER BRIGHT BLUE) UNTUK PERIKANAN BAGAN APUNG DI PERAIRAN PATEK KABUPATEN ACEH JAYA PROPINSI ACEH - Taufiq Taufiq; Wazir Mawardi; Mulyono S Baskoro; Zulkarnain Zulkarnain (JURNAL PERIKANAN TROPIS, 2016)
Fishery potential utilization in the waters of Aceh Jaya was dependent on fishing technology and still limited.The type of fishing gears which used in Aceh Jaya were beach seine, line fishing, gillnet, and liftnet. Liftnet used by Patek fishermen was floating liftnet. Bagan was classified in light fishing. The type of lamps which used by fishermen was fluorescent and set on the surface, whereas the surface lamp was less effective for use. This research used underwater lamp. The aims of this research were to get underwater lamp construction and determine the LED effectiveness. Construction of underwater lamp designed an innovation, that was the dimmed, so that fish which have aggregated by the light would more focus to the liftnet. The research methods were descriptive, fishing gear construction design, experiment or experimental fishing. Underwater lamp lights could help Patek fishermen for fishing and  got maximum catches. Total catches by using fluorescent light were 2343 kg. Meanwhile, total catches with underwater lamp were 3779 kg. Fish species that were caught by lift net were anchovy, peperek, tembang, mackerel, selar, japuh, and layur for 10 trip, 5 trip in the dark and the bright moon. Seen that there were differences of catches amount and composition by using fluorescent lamps and underwater lamp. The results of research it was concluded effective underwater lamp as a tool in fisheries liftnet.